Impact of the COVID-19 pandemic in the Portuguese population: Consumption of alcohol, stimulant drinks, illegal substances, and pharmaceuticals - Fernandes, S (2021)
Background The measures implemented by governments worldwide to control and prevent the spread of the COVID-19 have impacted the populations and directly influenced individuals’ quality of life and consumption habits. Objective This work investigates the Portuguese population’s changes in alcohol, stimulants drinks, illegal substances, and pharmaceutical consumptions habits during the COVID-19 pandemic. Methods An online questionnaire comprising seven groups of questions–with one group referring to alcohol, stimulant drinks, illegal substances, and pharmaceuticals consumption habits–was made available to the general adult population of mainland Portugal from the 26th January through the 31st of March 2021. After applying the inclusion criteria, 1666 questionnaires were selected and analysed using descriptive and inferential statistics. Results Our results show that 48.9% of the participants have alcohol drinking habits and increased their alcohol consumption by 16% after the beginning of the COVID-19 pandemic lockdown. Furthermore, 8.7% of the respondents felt the need to increase their consumption of stimulant drinks, especially coffee, the most consumed stimulant drink (77.9%). We also observed that of the 3.1% of respondents who are usual consumers of illegal substances, 26.9% increased their consumption of these substances during the COVID-19 pandemic. Concerning pharmaceuticals, 23.2% of the respondents expressed their need to take a therapeutic drug after the start of the COVID-19 pandemic. The profile of common consumers of alcohol, stimulant drinks, illegal substances, and pharmaceuticals in the COVID-19 pandemic context is contrasting and varies according to gender, age, and employment status. Conclusions The COVID-19 pandemic led to an increase in the consumption of alcohol, stimulant drinks, illegal substances, and pharmaceuticals prescribed to treat anxiety, depression, and sleep changes in the Portuguese population. These new consumption patterns have probably aggravated domestic violence, mental diseases, and impairment of family quality of life in the Portuguese population.